2020
DOI: 10.1002/ehf2.12915
|View full text |Cite
|
Sign up to set email alerts
|

ZSF1 rat as animal model for HFpEF: Development of reduced diastolic function and skeletal muscle dysfunction

Abstract: Aims The prevalence of heart failure with preserved ejection fraction (HFpEF) is still increasing, and so far, no pharmaceutical treatment has proven to be effective. A key obstacle for testing new pharmaceutical substances is the availability of suitable animal models for HFpEF, which realistically reflect the clinical picture. The aim of the present study was to characterize the development of HFpEF and skeletal muscle (SM) dysfunction in ZSF1 rats over time. Methods and results Echocardiography and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 50 publications
7
77
1
Order By: Relevance
“…This allowed various sites in the muscle contractile process to be evaluated for dysfunction in HFpEF, including neuromuscular transmission and excitation-contraction coupling. Consistent with previous data where absolute maximal soleus force was reduced by ∼20% in HFpEF rats vs. controls (Bowen et al 2018;Schauer et al 2020), we observed that absolute twitch and maximal forces in both the soleus and EDL were lower in HFpEF rats. However, limb muscle weakness was closely associated with fibre atrophy as, after normalising for muscle mass, specific forces were not different between groups independent of whether the neural and blood supply remained intact.…”
Section: Impact Of Hfpef On Limb Muscle Functionsupporting
confidence: 92%
See 4 more Smart Citations
“…This allowed various sites in the muscle contractile process to be evaluated for dysfunction in HFpEF, including neuromuscular transmission and excitation-contraction coupling. Consistent with previous data where absolute maximal soleus force was reduced by ∼20% in HFpEF rats vs. controls (Bowen et al 2018;Schauer et al 2020), we observed that absolute twitch and maximal forces in both the soleus and EDL were lower in HFpEF rats. However, limb muscle weakness was closely associated with fibre atrophy as, after normalising for muscle mass, specific forces were not different between groups independent of whether the neural and blood supply remained intact.…”
Section: Impact Of Hfpef On Limb Muscle Functionsupporting
confidence: 92%
“…As previously noted (Leite et al 2015;Franssen et al 2016;van Dijk et al 2016;Bowen et al 2017b;Schauer et al 2020), by 20 weeks of age obese-ZSF1 rats have developed typical metabolic signs associated with HFpEF including obesity (P < 0.001; Fig. 1A), hyperglycaemia (P < 0.001; Fig.…”
Section: Cardiometabolic Phenotypesupporting
confidence: 77%
See 3 more Smart Citations